Speaking Problems Faced By Efl Learners In Individual Presentation - Himmah, Nihayatul; Mahdavi, Milad; Bakhtiari, Somayeh (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This study was aimed to know speaking problems faced by EFL learners in individual presentation at 4th semester English department students of UIN Walisongo Semarang. The method used in this study was qualitative method with descriptive approach. The data was collected from all members of PBI-4C. Methodology: The data were gathered through in-depth interview, observation and documentation. The results of the study were shown in three factors; they are linguistic knowledge point of view (vocabularies, pronunciation, and grammar), psychological point of view (lack of confidence, shyness, nervous, fear of mistake, and confuse) and non-linguistic knowledge (lack of preparation, lack of motivation and teaching vocabulary). Main Findings: The findings suggest that the teacher should pay attention more to students’ awareness for speaking ability, moreover, it is in presentation skill which is clearly and understandable. Finally, English speaking problems in this university will decrease and students are able to speak up in front of public and also have better performance in speaking in the future. Novelty/Originality of this study: This study offers a fresh perspective by focusing specifically on the speaking problems encountered by EFL learners during individual presentations, a context that demands both linguistic competence and performance skills. Unlike general speaking studies, it highlights real-time anxiety, organization, and fluency issues, thus advancing existing knowledge by linking language proficiency with presentation-specific challenges in academic settings.